EKSPLORASI ETNOMATEMATIKA PADA BAJU BATIK NIAS UTARA - Magdalena Susanti Telaumbanua; Derman Buulolo; Dedi Presli Halawa; Tutiarni Naibaho; Ruthmayasari Simanjuntak (Ndrumi : Jurnal Ilmu Pendidikan dan Humaniora, 2023)
Indonesia has been recognized by the world as a nation that has many uniqueness. One of the characteristics of the well-known Indonesian nation is batik. The aim of this study was to analyze how the patterns, symbols and mathematical motifs in North Nias batik are used and interpreted by Nias people in their cultural context. Almost all regions in Indonesia have typical batik which is a special characteristic of the area. Likewise with North Nias who recently launched Batik which is the hallmark of North Nias district, starting from the colors and also the motifs. North Nias batik motifs have unique patterns and if observed and analyzed have a relationship with mathematical concepts. The mathematical concepts that exist in North Nias batik motifs are related to congruence, flat shapes, geometric transformations. The research subjects could consist of North Nias traditional clothing makers, artists or Nias community leaders who have knowledge about the design and use of North Nias traditional clothing.